ACADEMIC WRITING CHALLENGES OF FOREIGN LANGUAGE LEARNERS IN PAKISTAN - Dr. Syeda Naureen Mumtaz (Journal of Arts & Social Sciences, 2021)
This descriptive qualitative research sought to explore as what would be the best writing approach adopted to teach academic writing skill to the undergraduate university students to identify and minimize the identified problems. The aim of the study was to strengthen the academic writing skill of university students. For this purpose, thirty undergraduate students were selected and involved in focus group discussions to highlight the problematic area in the field of academic writing. Thematic analysis helped to understand the problems faced by the students and suggestions were made on the basis of the study’s findings. The study revealed the students’ inability to use appropriate vocabulary. These students lacked the skill to express themselves in their own words, and often their written work would look patchy. English being the foreign language to the students hampered their ability to think in the target language. The present study contributed to understand the problems and suggested process approach of writing to be adopted by the faculty to overcome the academic writing related problems.Key Words: Process Approach, Product Approach, Genre Approach, Academic Writing